Methodological aspects of estimating the prospects of subsoil plots through ontological engineering - Dadykin, V. S.; Dadykina, O. V.; Geraschenkova, T. M.; Skantsev, V. M. (SPIE, 2023)
Estimating the prognostic potential is also based on evaluating the geological potential, taking into account the available geological and economic information on this territory and the existing need for relevant resources. Thus, to make a decision on investing in further exploration on promising subsoil areas, it is necessary to consider a significant number of factors and their corresponding indicators. In such situations, it is customary to use knowledge bases built upon ontological engineering. As a result, it becomes possible to implement the obtained ontological model having a set of geological and economic parameters for estimating expected resources with the integration of the mathematical apparatus of fuzzy logic and set theory. Thus, the authors have considered the methodological aspects of estimating the prospects of the subsoil plots through ontological engineering of geological exploration, taking into account their features, based on using a knowledge base containing a thesaurus of geological and economic indicators by the exploration process stages. The links of geological and economic indicators as part of the subject area thesaurus are determined in order to build an ontological model, which makes it possible to perform factorial economic analysis. The actual evaluation of indicators as part of the thesaurus of the geological and economic assessment of the geological exploration results allows one to characterise the state of the study object and to proceed to estimating the volume of mining commodity output, according to the requirements of the individual territory, region, state (taking into account the volume of exports and imports) of mineral raw materials.